Comparison of the hemodynamic changes between preeclamptic and normotensive parturients who underwent cesarean section under spinal anesthesia at North Showa zone public hospitals, Oromia region, Ethiopia, 2022: a prospective cohort study - Bizuwork Girma Belachew; Blen Kassahun Dessu; Birhanu Wondimeneh Demissie; Ashagrie Sintayhu; Getahun Dendir; Abas Ali; Redi Awol; Dugo Angasa; Asaminew Tasew; Oliyad Eshatu; Aschalew Besha Desta; Derara Girma; et al. (BMC Anesthesiology)
Abstract Background Spinal anaesthesia complicates maternal hemodynamic and may expose the parturient to dangerous cardiovascular problems. Up to 7% to 89.2% of pregnant women can suffer from spinal anaesthesia-related hypotension. The aim of this study to compare the hemodynamic changes between preeclamptic and normotensive parturients who underwent caesarean section under spinal anaesthesia at North Showa Zone Public Hospitals, Oromia Region, from February 15 to May 15, 2022. Methods A prospective cohort study was conducted on a total of 140 parturients (70 in each group) who underwent cesarean delivery under spinal anesthesia. The study participants were chosen using a consecutive sampling technique. Data were collected from patient charts and intraoperative observations and entered into the Epi Data software version 4.6 and exported to the Statistical Package for the Social Sciences version 25 software. Hemodynamic change = (baseline value-current value/baseline value) * 100. The independent t-test, Mann–Whitney U test, two ways mixed ANOVA, chi-square, and Fisher's exact test was used to analyze the data as appropriate. A P < 0.05 was statistically significant. Results The mean percentage change in SBP, DBP, and MAP after spinal anaesthesia was a statistically significant difference between the normotensive and preeclamptic groups, except MAP at 15 min was comparable between the two groups with p = 0.638. The proportion of preeclamptic parturients who develop hypotension was 47%, compared to 74% of normotensive parturients, and the RR of developing hypotension, if participants were preeclamptic, was 0.63, with a 95% confidence interval of 0.412 to 0.978 and a p = 0.039. The mean change in heart rate during the first 15 min was comparable between the groups. Conclusion In contrast to normotensive parturients undergoing caesarean section under spinal anaesthesia, our study found that the hemodynamic change was lower in preeclamptic parturients. The proportion of preeclamptic women who develop hypotension was 47%, compared to 74% of normotensive parturients.